Text messaging and financial incentives to encourage weight loss in men with obesity: the Game of Stones feasibility RCT - Stephan U Dombrowski; Matthew McDonald; Marjon van der Pol; Mark Grindle; Alison Avenell; Paula Carroll; Eileen Calveley; Andrew Elders; Nicola Glennie; Cindy M Gray; Fiona M Harris; Adrian Hapca; et al. (Public Health Research, 2020)
Background: In 2016, 26% of UK men were estimated to be obese. Systematic reviews suggest that few men engage in formal weight loss interventions that support weight reduction and improve health. Objective: To co-produce, with patient and public involvement, an acceptable and feasible randomised controlled trial design to test a men-only weight management intervention. Design: This was a two-phase feasibility study. Phase 1 was the development of intervention components, study procedures and materials including a discrete choice experiment with survey questions. Phase 2 was an individually randomised three-arm feasibility trial over 12 months. Qualitative interviews were conducted at 3 and 12 months. Setting: The setting was two sites in Scotland that had disadvantaged urban and rural areas and differed in employment levels and ethnic groups. Participants: In phase 1, 1045 men with obesity were recruited by Ipsos MORI (London, UK; www.ipsos.com/ipsos-mori/en-uk) to represent the UK population. In phase 2, 105 men with obesity were recruited in the community or through general practice obesity registers. Qualitative interviews were conducted with 50 men at 3 months and with 33 men at 12 months. Interventions: The trial arms were narrative short message service (SMS) for 12 months (SMS only), financial endowment incentive informed by loss aversion and linked to achievement of weight loss targets plus narrative SMS for 12 months (SMS + I), and waiting list control group for 12 months followed by 3 months of an alternative SMS style developed based on feedback from men who had received the narrative SMS (control). Main outcome measures: The main outcome measures were acceptability and feasibility of recruitment, retention, engagement, intervention components and trial procedures. Outcomes were assessed by examining procedural, quantitative and qualitative data at 3, 6 and 12 months. Results: The most acceptable incentive strategy, based on the discrete choice experiment results, was to verify weight loss of 5% at 3 months, verify weight loss of 10% at 6 months and maintain weight loss of 10% at 12 months. Overall, 105 men with obesity from across the socioeconomic spectrum were successfully recruited to target, 59% of whom lived in more disadvantaged areas. Retention at 12 months was acceptable (74%) and was higher among individuals from disadvantaged areas. Narrative SMS were acceptable to many men, with a minority reporting negative reactions. Incentives were acceptable but were not the primary motivation for behaviour change. Twelve men in the incentive arm (33%) secured at least some money and three (8%) secured the full amount. Both intervention arms lost some weight, with greater weight loss in the arm that received SMS and incentives. The alternative SMS based on men’s feedback received no strong negative reactions. Limitations: Fewer participants from the SMS + I arm (64%) completed the study at 12 months than did those in the SMS-only (79%) and control (83%) arms. The reasons for this difference were complex. Conclusions: The men-only weight management intervention consisting of narrative SMS and financial incentives was acceptable and feasible, meeting the progression criteria for a full trial. Tailoring of SMS may improve acceptability and retention. Future work: Minor refinements to the intervention components based on the study findings will be made prior to testing in a multisite definitive randomised controlled trial. Trial registration: ClinicalTrials.gov NCT03040518. Funding: This project was funded by the National Institute for Health Research (NIHR) Public Health Research programme and will be published in full in Public Health Research; Vol. 8, No. 11. See the NIHR Journals Library website for further project information.